2021
DOI: 10.1177/21582440211008422
|View full text |Cite
|
Sign up to set email alerts
|

Millennials as Dictionary Users: A Study of Dictionary Use Habits of Serbian EFL Students

Abstract: The article addresses the use of dictionaries among the new millennium generation of English as a foreign language (EFL) undergraduates. Applying the mixed-method approach (a questionnaire and interviews), the study examines the frequency of dictionary use, the types of dictionaries used, activities initiating dictionary consultation, information searched for, and problems faced in using dictionaries. The findings suggest that the participants are most fond of bilingual online dictionaries and use them mostly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
12
0
3
Order By: Relevance
“…In recent years, a body of research has addressed dictionary use in language settings (Alhatmi, 2019;Chen, 2016;Knežević et al, 2021;Li, 2019;Takkaç-Tulgar, 2017). Although the literature covers mainly monolingual and bilingual dictionaries, this review will focus on four major themes directly related to the scope of this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, a body of research has addressed dictionary use in language settings (Alhatmi, 2019;Chen, 2016;Knežević et al, 2021;Li, 2019;Takkaç-Tulgar, 2017). Although the literature covers mainly monolingual and bilingual dictionaries, this review will focus on four major themes directly related to the scope of this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They can increase learning motivation, and students can study independently (Dashtestani, 2013). Empirical evidence also indicates that language learners generally prefer bilingual to monolingual dictionaries because a native language equivalent usually is far easier to understand and process than a definition in the foreign language (Knezevic et al, 2021). Another study found that specialized dictionaries enhance the students' learning outcomes (Milić et al, 2018).…”
Section: Printed and Digital Dictionarymentioning
confidence: 99%
“…Estudios que han abordado cuáles eran las preferencias del usuario han comprobado que el prestigio del diccionario cuenta, pero sin llegar a ser un factor desequilibrante frente a la posibilidad de una descarga o una consulta gratis (Méndez Santos y Sala Caja, 2019). De hecho, se ha constatado que buena de los usuarios ni siquiera sabe el nombre de los que emplea (Nomdedeu, 2019;Knežević, 2021). 14 Collins (2016) comenta que un 37% de los que poseían un DEP no lo usaban nunca y destaca que los argumentos del debate papel vs. electrónico se han desplazado a DEP vs. diccionarios online en lo que respecta a la portabilidad, la inmediatez, la accesibilidad y facilidad de la búsqueda.…”
Section: Reputaciónunclassified